2022
DOI: 10.1177/03000605221097486
|View full text |Cite
|
Sign up to set email alerts
|

MTRR rs1532268 polymorphism and gastric cancer risk: evidence from a meta-analysis

Abstract: Objective The methionine synthase reductase ( MTRR) gene encodes the MTRR enzyme involved in the metabolic pathway of homocysteine. Several studies investigated the effect of the MTRR rs1532268 gene polymorphism on the risk of gastric cancer (GC), but the results have been inconsistent. Methods We performed a comprehensive and systematic search of PubMed, Google Scholar, MEDLINE, Science Direct, Scopus, CNKI, and Web of Science. Five studies were included in this meta-analysis to determine whether MTRR rs15322… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The inconsistent results may be explained by racial differences, differences in study design, and the presence of bias. In addition, several studies con rmed that MTRR gene polymorphisms were also associated with a variety of cancers [33][34][35], reproductive disorders[36] and cleft lip and palate [37]. However, most of the previous studies only focused on two loci (i.e., rs1801394 and rs1532268).…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent results may be explained by racial differences, differences in study design, and the presence of bias. In addition, several studies con rmed that MTRR gene polymorphisms were also associated with a variety of cancers [33][34][35], reproductive disorders[36] and cleft lip and palate [37]. However, most of the previous studies only focused on two loci (i.e., rs1801394 and rs1532268).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical heterogeneity among studies was evaluated using I 2 statistics (ranges from 0 to 100 %), λ 2 test, and P -values. [ 17 ] The fixed effects model method was used, except when a significant Q test ( P < .05) or I 2 > 50 % indicated the existence of heterogeneity among studies, when it was indicated the existence of heterogeneity, the random effects model was applied. [ 17 ] Heterogeneity was also explored in subgroup analysis with ethnic groups (Asian and Caucasian).…”
Section: Methodsmentioning
confidence: 99%
“…[ 17 ] The fixed effects model method was used, except when a significant Q test ( P < .05) or I 2 > 50 % indicated the existence of heterogeneity among studies, when it was indicated the existence of heterogeneity, the random effects model was applied. [ 17 ] Heterogeneity was also explored in subgroup analysis with ethnic groups (Asian and Caucasian). Funnel plots were drawn to estimate the potential publication bias, in which the standard error of log (OR) of each study was plotted against its log (OR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTRR gene codes methionine synthase reductase (MTRR) enzyme,[ 9 ] which is necessary for the regeneration of functional methionine synthase (MS) by reductive methylation in which the methyl donor is S-adenosylmethionine (SAM). The prevalent SNP in the MTRR gene is the substitution of G for A at position 66 which causes isoleucine to methionine substitution.…”
Section: Introductionmentioning
confidence: 99%